2008
DOI: 10.1108/02683940810869015
|View full text |Cite
|
Sign up to set email alerts
|

Older workers' motivation to continue to work: five meanings of age

Abstract: Little is known about the motivation for older workers to work and to remain active in the labor market. Research on age and motivation is limited and, moreover, conceptually diverse. In this study, we address age-related factors that influence the work motivation of older workers. More specifically, we examine how various conceptualizations of the age factor affect the direction and termination of the motivation to continue to work of older workers. Methodology: A literature review of age-related factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
474
5
28

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 502 publications
(520 citation statements)
references
References 105 publications
(146 reference statements)
13
474
5
28
Order By: Relevance
“…These observations were found across physical, cognitive and personality domains, and has led to the introduction of the notion of increasing heterogeneity with age in gerontological research as well as HRM research (Kooij et al, 2008). Subsequent work extended this perspective, and concluded that with increasing age, people become more different from their age-related peers (Dannefer, 2003).…”
Section: The Theory Of Aged Heterogeneitymentioning
confidence: 86%
See 3 more Smart Citations
“…These observations were found across physical, cognitive and personality domains, and has led to the introduction of the notion of increasing heterogeneity with age in gerontological research as well as HRM research (Kooij et al, 2008). Subsequent work extended this perspective, and concluded that with increasing age, people become more different from their age-related peers (Dannefer, 2003).…”
Section: The Theory Of Aged Heterogeneitymentioning
confidence: 86%
“…Subsequent work extended this perspective, and concluded that with increasing age, people become more different from their age-related peers (Dannefer, 2003). This idea has also been integrated implicitly in theory on aging at work, which assumes that older workers may have large variations in their physical, psychological, and other capabilities (Kooij et al, 2008). While younger workers may be more alike in what they expect from their work, and what their work capabilities are, older workers tend to be more different from each other in those respects.…”
Section: The Theory Of Aged Heterogeneitymentioning
confidence: 89%
See 2 more Smart Citations
“…Psychosocial age is related to the self and the social perception of age: subjective age defines how old a person feels, with which age cohort he or she identifies, and how old he or she desires to be, whereas the social perception of age focuses, for example, on the age at which society perceives an individual to be older, the definitions and stereotypes of older employees and the implications for HR decisions of labelling an employee as older. (Kooij et al, 2008;Uotinen, 2005;Laslett, 1989;Doering et al, 1983. ) Organizational age refers to seniority and organizational tenure, but it can also refer to career stage, skill obsolescence and age norms within the organization (Kooij et al, 2008).…”
Section: Ageing and Gender In The Field Of Hrmmentioning
confidence: 99%